Interconnections : bridges, routers, switches, and internetworking protocols - Perlman, Radia (Reading, Mass. ; Harlow : Addison Wesley, 2000)
A text on networking theory and practice, providing information on general networking concepts, routing algorithms and protocols, addressing, and mechanics of bridges, routers, switches, and hubs. Describes all major network algorithms and protocols in use today, and explores engineering trade-offs that each different approach represents.
Includes index.
oif 17/02/15
Loan
Keywords: Computer network protocols; Bridges (computer networks); Local area networks (computer networks); Routers (computer networks); Interconnections